Android-based Dental Anatomy Learning Application Using Mayer’s Multimedia Learning Principles - Deka Desilawati; Haris Setyawan; Reza Giga Isnanda (Emerging Information Science and Technology, 2020)
Anatomy learning methods are still dominated by using books, in which the material is presented in pictures and writings. The anatomy learning method using books is carried out by redrawing parts and memorizing the location and its terms. Thus, students have difficulties when they forget and want to find terms on the anatomy because it is uneasy and takes a long time. This research aims to create a system to study anatomy, especially dental anatomy, through an android-based application, and provide ease of anatomy of tooth learning using Mayer’s principle of multimedia learning on application. Based on system testing and user testing results, this application can be used as a medium of information and learning about tooth anatomy. It is evidenced by black-box testing and questionnaire results.